Analysis Influence Various Types of Promotions Sale To Behavior Purchase Consumers : Case Study at Niaga Supermarket , Lombok - suleman, Dede; Sabil, Sabil; Ati Haryati, Raden; Wianti, Wiwin; Sofyanty, Devy (Dinasti International Journal of Management Science, 2024)
Research This aim For investigate impact various type promotion sale to behavior purchase consumers at Niaga Supermarket , Lombok. Through analysis of survey data involving sample consumer from the supermarket , research This disclose relevant findings . _ Research result show that promotion " buy one free one " have influence weak positive _ to behavior purchase consumer . Discount price , on the other hand , has influence more positive _ moderate to behavior purchase . Coupons also have an impact behavior purchase in a way positive with level moderate influence , meanwhile _ free samples no proven own significant impact on behavior _ purchase . Interestingly , the bonus pack, though often used in practice promotion sales , have influence weak negative and no _ significant on behavior purchase consumer . This result give outlook valuable for practitioner marketing and research furthermore about type promotion most effective sales in influence behavior purchase consumers in a supermarket environment . With more understanding _ deep about preference consumer related promotion sales , marketer can devise more strategies appropriate , temporary consumer can make decision more purchases _ informant .